Reducing the burden of iron deficiency anemia in Cote D'Ivoire through fortification - Alberto Prieto-Patron; Zsuzsa V. Hutton; Giovanni Fattore; Magalie Sabatier; Patrick Detzel (BMC, 2020)
Abstract Background Iron deficiency anemia (IDA) is highly prevalent in the Cote d'Ivoire and has severe health and economic consequences. In this paper, we apply a health economic model to quantify the burden of IDA, and the contribution of nationwide mandatory iron fortification of wheat flour and voluntary iron fortification of condiments to the reduction of this burden. Methods The analysis for the population from 6 months to 64 years builds on published reviews and publicly available datasets and is stratified by age-groups and socioeconomic strata using comparative risk assessment model. Results Without the impact of these fortification strategies, the annual burden of IDA is estimated at 242,100 disability adjusted life years (DALYs) and 978.1 million USD. Wheat flour and condiment fortification contributed to a reduction of the IDA burden by approximately 5% each. Conclusion In places with high prevalence of malaria and other infectious diseases, such as the Côte D'Ivoire, food fortification as a nutritional intervention should be accompanied with infectious disease prevention and control. The findings of this study provide additional input for policy makers about the magnitude of the impact and can support the conception of future fortification strategies.